Diskrepansi Umaro dan Tokoh Agama di Masa Pandemi Covid 19 (Studi Deskriptif Analisis Di Masjid Al-Hidayah Desa Sukamukti Kec. Cikijing Kab. Majalengka) - Helmi Prihandani; Mas’ud Dzakiri; Khaerul Wahidin; Muhammad Azka Maulana (AL-MUFASSIR, 2020)
The research we conducted was motivated by the existence of two disagreements between Jamaahs of the Al-Hidayah mosque in Sukamukti Village, Cikijing District, Majalengka Regency in responding to the circular letter of the Regent of Majalengka Number 400/646/Kesra regarding the Guidelines for Romadhon worship and Eid al-Fitr whether to follow the government's recommendation that said that during the Covid-19 pandemic all routine worship activities that are usually carried out in mosques such as congregational prayers, routine recitations, Friday prayers, tarawih prayers and Eid prayers are carried out at home or are the calls of religious leaders inviting their congregation to continue carrying out routine worship as usual at mosque. The method used in this research is descriptive qualitative method. Namely by utilizing qualitative data obtained from interviews with religious leaders, representatives of the village government and congregations of mosques. From the results of the research, it turns out that the congregation of the Jami Al Hidayah mosque prefers to follow the recommendations of religious leaders than to follow the recommendations of the Regent of Majalengka. From this the author knows that in fact the religious leaders are more obeyed than those in the government sector